Kontribusi Disiplin Kerja dan Motivasi terhadap Produktivitas Karyawan PT PNM Mekar Syariah di Cilodong Kota Depok - Salsabila Septarina; Teul Panda Banjal (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Teknologi Nusantara, 2025)
The purpose of this study was to determine the effect of work discipline and motivation on employee performance at PT PNM Mekar Syariah in Cilodong, Depok City. The method used is quantitative. The sampling technique used saturated sampling, namely 53 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient and hypothesis test. The results of this study are Work discipline has a significant effect on employee performance with a determination coefficient value of 46.9% and the hypothesis test obtained t count> t table or (6.706> 2.008). Motivation has a significant effect on employee performance with a determination coefficient value of 36.4% and the hypothesis test obtained t count> t table or (5.408> 2.008). Work discipline and motivation simultaneously have a significant effect on employee performance with a regression equation Y = 11.586 + 0.400X1 + 0.310X2. The coefficient of determination value is 59.0% while the remaining 41.0% is influenced by other factors. The hypothesis test obtained the calculated F value > F table or (36.029 > 2.790).